Pedagogical activity of academic B.Y. Wedeneev - Karadobrii, T. A. (History of science and technology, 2013)
The pedagogical activity of prominent domestic power engineering specialist and natural scientist B.Y. Wedeneev is discussed in the paper. The basic stages of his pedagogical work, participating in education of rising generation of power engineering specialists, are described.